Determination of the Main Components of Essential Oil Extracted from( Aloysia citriodora L.) (Damascus University Journal of agriculture sciences, 2021)
Due to the economical and medical importance of lemon verbena  plant, and the wide distribution of this plant in Syrian environment, samples of Aloysia citriodora L. (Verbinaceae) were gathered randomly during 2011-2012 from Drekish and Bosra Alsham regions to extract the essential oil and determine the main components by using Gas Chromatography GC-MS.The results showed that the percentage of the essential oil ranged from 0.36 to 0.42%. The analysis of essential oil showed that the main active components were Limonene, Citral, Spathulenol, b-citral, and Limonene was the main component
Keywords: Aloysia citriodora L; Essential oil; Limonene; Medicinal plants